PEMANFAATAN KOLEKSI PERPUSTAKAAN DALAM MENINGKATKAN KETERAMPILAN SISWA SMKS PARIWISATA TRIATMA JAYA SINGARAJA, BALI - Putu Septhia Maharani (ACARYA PUSTAKA, 2025)
The objectives of this study were; (1) To determine the utilization of the collection inimproving the skills of vocational students at the Triatma Jaya Singaraja Tourism SMKSschool, (2) To find out the obstacles of Triatma Jaya Singaraja Tourism SMKS students inutilizing the collection in their library. The research method in this study is to use descriptivequalitative research methods with informant determination techniques, namely purposivesampling with snowball sampling. This research was conducted at Triatma Jaya SingarajaTourism High School. The data collection techniques that researchers use are observationtechniques, interviews, and document studies to facilitate obtaining data at the research site.The results of the research obtained by the researchers said that the library collection of TriatmaJaya Singaraja Tourism SMKS could not be maximally utilized to improve student skills at theTriatma Jaya Singaraja Tourism SMKS school. The library collection of Triatma Jaya SingarajaTourism SMKS still needs additional collections, both from the hospitality department and theculinary department. In addition to library collections that cannot be maximally utilized, thereare also obstacles faced by students of Triatma Jaya Singaraja Tourism SMKS in utilizing thecollection, including limited library collections, damaged book collections, and librarylocations that are far from the reach of students.